The Influence of NiTi File Design Features on the Apically Extruded Debris During Endodontic Treatment A concise reviews (Mustansiria Dental Journal, 2023)
Expelling debris and irrigating solution during cleaning and shaping is an inevitable incidence during endodontic treatment. Any irritation of the periapical area can initiate a flareup situation which can affect the prognosis of endodontic treatment. Thus, Controlling the amount of apically extruded debris increases the success rate of endodontic treatment. Furthermore, the incidence of flare-ups during endodontic treatment can be reduced by selecting the NiTi file system with the lowest apically extruded debris. Despite the advances in endodontic file design that aims to conservatively prepare the apical third of root canals, extruding debris toward the apex is still a non-eliminated issue with all instrumentation systems. The purpose of this review is to identify the effect of each design characteristic on the amount of debris expelled beyond the apical foramen. The strategy of this review focused on reviewing specific electronic databases, time, keywords, and standardized methods. Literature reviewing included studies from almost 20 years ago and up to 2022. In conclusion,  the design of the NiTi endodontic file has a significant impact on the amount of apically extruded debris.